2011
DOI: 10.4103/0019-5154.91830
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of quality of life in psoriasis patients: A cluster analysis of 50 patients

Abstract: Background:Although psoriasis generally does not affect survival, it certainly has a number of major negative effects on patients, demonstrable by a significant detriment to quality of life.Aims:We have done a study with the objective of assessing the clinical variables adversely affecting quality of life in patients diagnosed with psoriasis.Materials and Methods:This study is a cluster analysis of 50 consecutive consenting patients with psoriasis, of both sexes, aged over 18 years, attending the dermatology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
3
10
0
2
Order By: Relevance
“…The more patients with psoriasis showed behavior aimed at avoiding too strong negative emotions, stress and tension the more often they indicated higher quality of life and satisfaction with their health condition. The observed relationships are consistent with the reports of other researchers who have shown that psychological factors may influence the severity of skin changes in psoriasis [8,9]. The foregoing relationship is especially associated with stressors and ability to cope with stress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The more patients with psoriasis showed behavior aimed at avoiding too strong negative emotions, stress and tension the more often they indicated higher quality of life and satisfaction with their health condition. The observed relationships are consistent with the reports of other researchers who have shown that psychological factors may influence the severity of skin changes in psoriasis [8,9]. The foregoing relationship is especially associated with stressors and ability to cope with stress.…”
Section: Discussionsupporting
confidence: 91%
“…During recent years scientists have attempted to identify behavioral markers which may directly or indirectly contribute to the severity of skin changes in psoriasis. It is suggested that undertaking activities with positive effect on health while limiting anti-healthy behaviors may reduce the severity of symptoms [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Lokalize eritemli skuamlı plaklardan jeneralize şiddetli tutuluma kadar değişen klinikte seyredebilen psoriasis, remisyon ve nüks dönemleri ile hayat boyu devam edebilir ve tam iyileşme nadiren sağlanabilir [4][5][6] . Sıklıkla yaşam süresini etkilemez; ancak hastaların yaşam kalitesi üzerine olan etkisi oldukça dramatiktir [5][6][7] . Hastalar psoriasis lezyonları nedeniyle kendilerini toplumdan dışlanmış hissederler.…”
Section: Introductionunclassified
“…Also other studies have shown low self-esteem and high levels of anxiety due to emotions like anger and shame in patients with psoriasis resulting from changes in appearance (14,15). Different studies have found that symptoms' severity and the area of the skin affected can have impact on the QOL (8,9,(11)(12)(13)16). The more severe the symptoms, the more likely patients are to have working day off and decreased productivity (10,13).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the extent of reduction of HRQOL by psoriasis is similar to that caused by other chronic diseases such as diabetes, ischemic heart disease and cancers (6). Several studies have been conducted to measure the QOL of patients with psoriasis and its determinants (7)(8)(9)(10)(11)(12)(13). A systematic review of psoriatic patients' quality of life (QOL) indicated physical and emotional problems and poor functioning, and negative body and self-image in the affected people.…”
Section: Introductionmentioning
confidence: 99%